ATTITUDE OF WOMEN’S COLLEGE TEACHERS TOWARDS HEALTH INSURANCE POLICY –WITH SPECIAL REFERENCE TO MADURAI CITY - KUMARI, Dr.S.MEENA; NAGARAJAN, Dr.I.; VINOTH, Dr. M. (The journal of contemporary issues in business and government, 2021)
Insurance is the mechanism of risk sifting, a financial tool specially created to reduce the finance, impact of unexpected events that happens in every life. Wealth is an important factor of human resource development and good health is real wealth of society, the health is the state of being free from illness or injury. World Health Organization (WHO), defines it as a "State of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity". Health is a dynamic condition resulting from a body's constant adjustment and adaptation in response to stresses and changes in the environment for maintaining an inner equilibrium called homeostasis. This paper mainly focuses on the single women, stay-at-home mothers, married women, working women all of whom should have adequate insurance cover. It is the need of the hour, as it helps to safeguard their health, save money, and create a shield of protection. Women need more medical intervention than men because they require reproductive care and they tend to fall ill more often.